The invisible island - Roy, Ron, 1940- (Roy, Ron, 1940- A to Z mysteries., 1999)
While picnicking on Squaw Island, Dink, Josh, and Ruth Rose find a hundred dollar bill, and when they return to explore further they find an entire cave full of money.